An analysis of urban governance based on providing an optimal model (Case study of Garmadreh city) - Naser Mohamadi; Hosin Mojtabazadeh; ali tavakolan (تحقیقات کاربردی علوم جغرافیایی)
Proper urban management based on the right methods has always been a serious challenge for urban professionals and has been the subject of various discussions and studies over time. Each city, due to its specific characteristics, experiences special issues that are specific to the city and its surroundings, and in the meantime, creating a single model is not acceptable. Good urban governance is an important principle in urban management, which unfortunately In our country, it faces many obstacles. The present article has been done in terms of purpose, application-development and quantitative-analytical method, which first identifies the most important obstacles to the actual implementation of urban governance in the country and then examines these cases in the study area of ​​Garmadreh. The results show that the factor of lack of integration between different sectors of urban management with an average of 3.8 has the greatest impact on the lack of governance in the country. From the results of the first part, 4 basic effective indicators in the implementation of urban governance in the study area have been studied. In the executive level of Garmadreh city, in the field of accountability index of weakness factor in continuous and public supervision with an average rank of 5.38, in the index of rule of law rule, there are multiple, parallel, interpretable and sometimes contradictory laws with an average rank of 3.73, in the transparency index of factor of lack of access to information 4.56 And in the participation index, the factor of intense centralism and top-down management with an average rank of 4.48 have the greatest impact on the lack of proper implementation of urban governance in the city of Garmadreh.